Empirical evidence of fiscal culture in the traders of the popular market of Montería-Colombia (2023)
The study on tax culture focused on describing the main accounting and tax aspects presented by traders in the development of accounting and tax responsibility in Colombia. The methodology was based on the application of a survey-type instrument to 76 traders in the public market. The results reveal regarding the attitude towards tax evasion. A high level of knowledge on the part of taxpayers and a high level of social acceptance of tax evasion practices. Likewise, they consider that cheating in evasion would not generate discomfort on the part of the people around them and their families.